Efficacious lifestyle interventions for appropriate gestational weight gain in women with overweight or obesity set in the health care system: a scoping review. (12th December 2022) - Barroso, Cristina S.; Yockey, Andrew; Degon, Emoni; Gautam Poudel, Pragya; Brown, Susan D.; Hedderson, Monique M.; Moreno-Hunt, Carey; Ehrlich, Samantha F.
Abstract: Purpose: Health care systems offer opportunities to scale up interventions for appropriate gestational weight gain (GWG); however, GWG interventions in the health care setting remain largely unavailable to women with overweight or obesity. To inform the translation of efficacious lifestyle interventions to health care delivery systems, this scoping review aimed to systematically identify randomized controlled trials for appropriate GWG in women with overweight or obesity that were set in a health care system. Methods: A scoping review allows for the systematic synthesis of knowledge on an exploratory research question aimed at mapping key concepts (e.g. time, location, source, and evidence) and gaps in a specific area of study. The Colquhoun et al. (2014) framework to conducting scoping reviews was used to develop the research question, identify relevant studies, select studies, extract data, and synthesize data. Specifically, two reviewers searched publication databases for English-language articles published from January 2009 to May 2020 using specific keywords/MeSH terms. Results: Eight peer-reviewed journal articles were identified; six trials were based in Europe and two in the U.S. Only four included lifestyle interventions that were efficacious in reducing GWG. Three trials with efficacious interventions were among women with obesity only and encouraged them to gain at or below the lower limit for total GWG (i.e. ≤5 kg) of the Institute of Medicine (IOM) guidelines. The fourth was among women with overweight or obesity and encouraged women to gain within the IOM guidelines with a telehealth behavioral intervention. Efficacious interventions were initiated in the first half of pregnancy and included frequent contact delivered through multiple modalities (i.e. in-person visits, telephone calls, text messages, email) by trained intervention staff (i.e. dietitian, lifestyle coach, and/or physiotherapist). Only one efficacious intervention trial briefly mentioned theoretical components for health promotion (e.g. self-monitoring); likewise, only one included cost-effectiveness analyses. Conclusions: This review systematically identified randomized controlled trials of efficacious lifestyle interventions (i.e. consisting of diet and physical activity components) for appropriate GWG in women with overweight or obesity that were set in the health care system and delivered by non-clinicians. Translation efforts could draw upon aspects of the efficacious lifestyle interventions described in this review. Future studies should examine theory-based telehealth interventions and cost-effectiveness.